Faktor-faktor yang memengaruhi literasi matematika: systematic literature review - Anis Rahmanuri; Retno Winarni; Anesa Surya (Didaktika Dwija Indria, 2023)
Mathematical literacy is the ability to reason and use mathematical concepts to describe and interpret things in context. The study aims to systematically review the literature on factors related to mathematical literacy. The method used in this study is a systematic literature review with procedures including identifying, reviewing, evaluating, and interpreting research. A literature search was carried out via Google Scholar in the 2013–2023 period. The inclusion criteria were Indonesian-language articles that specifically discussed mathematical literacy and its influencing factors. Based on the reviewed articles, this study used four articles that met the requirements. The results of the review show that there are several factors related to mathematical literacy. These factors are classified into internal factors and external factors. The dominant factors that contribute to mathematical literacy are verbal ability as a cognitive aspect and mathematical disposition as a non-cognitive aspect. Thus, these two factors become predictors of mathematical literacy. These two factors can be studied further to determine the extent of their relationship with mathematical literacy. This research is a literature review for research related to factors in mathematical literacy.